Formulation and efficacy testing of vermi-tea based liquid organic fertilizers on green-amaranth (Amaranthus viridis L.) for home gardens - Pakeerathan, K.; Dayananda, A.N.P.E.; Viharnaa, R. (Eastern University, Sri Lanka, 2023)
Sudden food shortage due to strict green agriculture policy, economic crisis, COVID pandemic situation instruct the importance of home level organic production of good quality fruits and vegetables. Therefore, an experiment was conducted to test the efficacy of organic liquid fertilizers formulated from fish, livestock’s and plant wastes on leafy vegetable green Amaranth to promote home gardening. The liquid fertilizer was tested on Amaranth grown separately in vemicompost and garden compost. The 7 kg capacity pots were filled with two media (medium 1: vemicompost; medium 2: garden compost) and arranged in CRD with four replicates with each medium. Five plants of green-amaranth per pot were planted and treated with fish emulsion + vermi-tea (1:4=T1), cow urine + vermi-tea (1:4=T2), three leaves [Neem+ Giliricidia+ Candle bush] solution + vermi tea (3:1=T3), vermi tea (T4) and control (T5) at the rate of 50 mL/pot on 2nd , 4 th and 6th week after planting. Agronomic and yield data were collected and subjected to ANOVA using SAS. Tukey's HSD multiple comparison test and PROC CORR was used to determine the best treatment combination at P <0.05. The results revealed that there was significant difference in N, P and K content of the treatments tested. The plant height, leaf area, number of leaves, root shoot ratio was significantly higher in fish emulsion + vermi-tea (1:4) [T1] and cow urine + vermi-tea [T2] at 8th weeks after planting in vermi-compost medium. There was strong and positive correlation (R2 > 0.8) among yield parameters, and root: shoot ratio with N, P K content of the liquid fertilizers tested in vermi-compost medium. Therefore, this investigation concludes that the fish emulsion + vermi-tea (1:4) and cow urine + vermi-tea (1:4) are good combination to use as liquid fertilizer at the rate of 50mL/Pot to get best yield in vermi- compost medium.
Keywords: Cow urine; Fish emulsion; Green-amaranth; Three leaves solution; Vermi-tea